PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTU MEDIA KARTU ARISAN DI KELAS V SDN 08/VI DESA PELANGKI - riska safira; zulqoidi R habibie; Refril dani (STKIP Subang, 2025)
The problem in this research is the low level of student learning process and outcomes in mathematics in grade V of SDN 08/IV Pelangki Village. This research aims to improve the learning process and outcomes of students in grade V of SDN 08/IV Pelangki Village, Batang Masumai District.This research is a classroom action research that examines the situation and conditions of the teaching and learning process at school. This research was conducted with 15 students in the first semester of the 2024/2025 academic year. The implementation of this research consisted of two cycles, each consisting of planning, implementation, observation, and reflection. The data were collected using quantitative and qualitative data analysis techniques. The results of this study can be explained as follows: (1) The application of the problem-based learning model, as seen from the learning process and outcomes in cycle I, with an average of 55.33%, experienced an increase in cycle II, namely an average of 80.66%. (2) The application of the problem-based learning model, as seen from the observation sheet, namely cycle I meeting I from the educator aspect with a value range of 75%, while cycle I meeting II with a value range of 75% and cycle II meeting I 80% and cycle II meeting II 85%. The student aspect of cycle I meeting I had an average value of 46%. While cycle I meeting II had a value range of 60%. And in cycle II there was an increase in the student aspect of cycle II meeting I reaching an average value of 80%. While cycle II meeting II reached an average of 93% with a very good category. It can be concluded that the application of the problem-based learning model can improve the process and outcomes of mathematics learning